2017
DOI: 10.1021/acs.jpcb.7b02724
|View full text |Cite
|
Sign up to set email alerts
|

Time-Domain THz Spectroscopy Reveals Coupled Protein–Hydration Dielectric Response in Solutions of Native and Fibrils of Human Lysozyme

Abstract: Here we reveal details of the interaction between human lysozyme proteins, both native and fibrils, and their water environment by intense terahertz time domain spectroscopy. With the aid of a rigorous dielectric model, we determine the amplitude and phase of the oscillating dipole induced by the THz field in the volume containing the protein and its hydration water. At low concentrations, the amplitude of this induced dipolar response decreases with increasing concentration. Beyond a certain threshold, markin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 59 publications
(137 reference statements)
3
31
0
Order By: Relevance
“…In contrast to this prediction, simulations 27,31 and absorption measurements for hydrated lysozyme 32 and for some amino acids 18 have suggested that the polarization of the interface can significantly deviate from the Maxwell scenario. We indeed show below that the so-called Lorentz void, 33 instead of the Maxwell void (Eq.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…In contrast to this prediction, simulations 27,31 and absorption measurements for hydrated lysozyme 32 and for some amino acids 18 have suggested that the polarization of the interface can significantly deviate from the Maxwell scenario. We indeed show below that the so-called Lorentz void, 33 instead of the Maxwell void (Eq.…”
mentioning
confidence: 90%
“…The experimental data 32 for the absorption coefficient of lysozyme were obtained by averaging absorption over the interval of frequencies 0.38 − 0.92 THz. There is therefore a sufficient frequency overlap between the data for bulk water 40 and solutions.…”
Section: Comparison To Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…the hydration shell, have a distinct absorption which differs from bulk water, consistent with previous studies of proteins in solution. 18,36,37,39 However, the manner in which water interacts with the two proteins is different, evidenced by the opposite behavior in a avg . Coupling of water to the protein depends upon its surface properties, in which the local topography influences interactions with water.…”
Section: Resultsmentioning
confidence: 99%
“…OR typically allows us to generate intense THz radiation below 5 THz (sketched in light green and light red in Figure 1c), while DFG covers higher frequencies (dark green and dark red in Figure 1c). Both inorganic (LiNbO 3 [66][67][68][69][70][71][72][73][74][75][76][77], GaSe [78][79][80], ZnTe [81,82], LiGaS 2 [83], GaP [84][85][86][87][88][89]) as well as organic (DSTMS [89][90][91][92], OH1 [93][94][95][96][97], DAST [98,99], DPFO [100], HMQ-TMS [101], OHQ-N2S [102]) crystals are phase-matched in the NIR and can emit pulsed THz fields with peak amplitudes in excess of 1 MV/cm. The approximate spectrum of the strongest THz pulses generated to date by non-linear optical methods in inorganic [62,64] and organic [63,65] crystals are shown in green and in red in Figure 1c, respectively.…”
Section: Introductionmentioning
confidence: 99%